Mixed time finite element formulations for dynamic problems - Sheng, Gang. (2009)
The time finite elements and the space-time finite elements have been emerging as modern tools for dynamic analysis. Just as their vital role in the evolution of spatial finite element, the variational formulations and weighted residual formulations play the fundamental and key role in the development of time finite elements. The aim of the present research is to put existing two-field mixed formulations of time finite element into a consistent context by introducing a series of comprehensively unified formulations.